Analysis of Synchronous Reluctance Machine With 3D-Printed Axially Laminated Rotor Featuring Axially Alternated Layers - Sitnikov, Maksim A.; Martin, Floran; Belahcen, Anouar (XXVIII. Symposium Electromagnetic Phenomena in Nonlinear Circuits (EPNC 2024): Conference Proceedings, 2025)
This study delves into the strategic layer alternation along the axial direction to mitigate electromagnetic torque ripple and minimize eddy current losses within synchronous reluctance electric machine with 3D-printed axially laminated rotor. A meticulous comparative analysis is conducted, scrutinizing the printing depth in the radial direction alongside variations in the number of alternating layers to discern the optimal ratio. Emphasis is placed on implementing two distinct 3D sliced models: one incorporating current continuity between slices and the other without. The article meticulously delineates the nuances of these models and draws a comprehensive comparison with a full 3D FEM model, elucidating their respective merits and drawbacks.